1985
DOI: 10.3109/10915818509014503
|View full text |Cite
|
Sign up to set email alerts
|

Sex and Age Differences in the Distribution of 14C-Sterigmatocystin in Immature and Mature Rats: A Multiple Dose Study

Abstract: Sterigmaltocystin, a secondary fungal metabolite, produces a toxic reaction upon administration to experimental animals. Examination of rats that have received multiple doses of ''C-sterigmatocystin may indicate the response elicited by repeated exposure to foodstuffs containing the mycotoxin. Daily doses of sterigmatocystin, 8 mg/kg equally divided over 13 days, 'were administered in the feed. Immature rats (50-150 g) and mature rats (200-300 g) of both sexes were studied. On the 14th day, an 8 mg/kg dose of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

1987
1987
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 5 publications
0
7
1
Order By: Relevance
“…Approximately 3% of the total STC administered was eliminated in the first 24 h. This value is considerably lower than the data obtained by Walkow et al (1985), when 14 C-labeled STC was used (8 mg/kg/13 days, administered in the feed); they found as much as 7.5 % of the total radioactivity in the first 24-h urine sample. Wang et al, (1991) described the excretion of radioactively labelled STC in rats after administration of 0.5 microCurie/g bw.…”
Section: Excretioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Approximately 3% of the total STC administered was eliminated in the first 24 h. This value is considerably lower than the data obtained by Walkow et al (1985), when 14 C-labeled STC was used (8 mg/kg/13 days, administered in the feed); they found as much as 7.5 % of the total radioactivity in the first 24-h urine sample. Wang et al, (1991) described the excretion of radioactively labelled STC in rats after administration of 0.5 microCurie/g bw.…”
Section: Excretioncontrasting
confidence: 56%
“…A study indicated that the volume of distribution of STC shows age and sex differences (Walkow et al, 1985). Oral administration to immature (50-150 g) and mature (200-300 g) rats of both sexes of 14 C-STC (8 mg/kg/13 days in feed and on the 14th day was orally intubated into the rats) resulted in plasma levels in male rats which were consistently higher than those found in the females.…”
Section: Absorption and Distributionmentioning
confidence: 99%
“…The highest level of tissue radioactivity was found in mature males and the lowest in immature females. Significant age differences were demonstrated, with tissue levels in different organs varying between mature and immature males and to a lesser extent between mature and immature females (Walkow et al, 1985).…”
Section: Distributionmentioning
confidence: 98%
“…The study of Walkow et al (1985) showed that most of the orally given STC in Sprague-Dawley rats was eliminated in the faeces (64-92 %), and about 10 % via urine. The calculated elimination half-life in these Sprague-Dawley rats varied between 61.5 h in immature females and 130 h in mature male rats and the cumulative total elimination rate (urine and faeces) after 96 h exceeded 99 % in immature and mature males, and varied between 71.5 and 77.4 % in immature and mature females, respectively.…”
Section: Excretionmentioning
confidence: 99%
See 1 more Smart Citation